Pembelajaran Materi Musik Tradisional Minangkabau - Fardha Dewi Sandra; Jagar Lumbantoruan (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out and describe how the implementation of learning traditional Minangkabau music material at UNP Laboratory Development High School. This type of research is qualitative research using descriptive methods. Data collection techniques are carried out through literature studies, interviews, observations, and documentation. Data analysis techniques are collecting data, classifying data, analyzing data, describing data and inferring data. The results showed that the lack of appropriate strategies and learning methods used by teachers. The strategy used by teachers in the learning process is an expository strategy, in the implementation of this expository strategy teachers use textbooks, references and other auxiliary media, but this strategy is not effectively used in learning because not all students are comfortable for learning that is only spoken. The method used in this learning is the lecture method, where learning is delivered by telling stories so as to make students feel bored and sleepy during learning, and it seems that the teacher has not been able to vary the method that is suitable for the implementation of traditional Minangkabau music learning which in fact in the delivery of learning can use several methods for the smooth achievement of the desired learning objectives.